Návrh změn systému hodnocení a odměňování zaměstnanců ve vybrané společnosti - Filipová, Silvie (Vysoké učení technické v Brně. Fakulta podnikatelská, 2013)
Bakalářská práce je zaměřena na oblast hodnocení a odměňování zaměstnanců ve společnosti Holík International, s.r.o. a následný návrh změn v této oblasti. Práce vychází z dotazníkového šetření a analýzy trhu práce, jež zajišťuje zjištění potřeb nynějších zaměstnanců. Na tomto základě je zpracován návrh ke změnám, který by mohl v budoucnu zajistit příchod nových a kvalifikovaných zaměstnanců.

This bachelor thesis is focused on evaluation and remuneration of employees in the company Holík International s.r.o. and on successive proposal of changes in this area. This thesis is based on the results of the survey and on analysis of the labor market, that provide finding of needs of the current employees. Proposal of changes is based on this survey and analysis of the labor market. That proposal of changes could provide the arrival of new qualified employees in the future.
Draft Amendments of the Evaluation and Remuneration of Employees in Selected Company
Keywords: Hodnocení; odměňování; mzda; zaměstnanecké benefity; zaměstnanci; SWOT analýza.; Evaluation; remuneration; salary; employee benefits; employees; SWOT analysis.